Investigating Resource Orchestration Affect the Performance of Young Entrepreneurs in Malaysia for Entrepreneurial Success - Nik Muhammad, Nik Maheran; Ridzwan, Rikinorhakis; Ab Rahman, Anis Amira; Nawi, Noorshiella Che (International Journal of Criminology and Sociology, 2022)
The process of resource orchestration is one of the great techniques in achieving better business performance. It covers the process of structuring, bundling and leveraging resources properly, strategically and innovatively. This study, therefore, aims to analyze the relationship between resource orchestration and entrepreneurial success. The data of young entrepreneurs from PUNB have been collected and analyzed using SPSS. The findings have found that resource orchestration has a significant effect on entrepreneurial success. Therefore, it can be concluded that the role of resource orchestration can help to improve business performance. If an entrepreneur can manage resources strategically beside exploiting creativity and innovation to gain a competitive advantage, then, prosperity will be achieved.